Recent Developments: Selling off the Plan (A Warning for Developers); Retirement Villages Act Amendments; Adverse Possession - Webb, E.; Levine, Pnina (Thomson Reuters (Professional), 2014)
Property lawyers in Western Australia have been busy keeping up-to-date with several new and interesting cases and some timely amendments to legislation. A recent decision of the Western Australian Court of Appeal has clarified a perplexing and long-uncertain issue involving s 13 of the Sale of Land Act 1970 (WA) and the validity of “off the plan” contracts when properties are sold prior to the developer becoming registered proprietor. In addition, the Supreme Court has considered a novel case about adverse possession where a plaintiff had acquired a mature possessory title which had not been converted to a registered title before the transfer to a Crown agency. The case is interesting as it considered the operation of both the 1935 and 2005 Limitation Acts and their respective operation in such circumstances. Finally, after much discussion and debate, Western Australia’s retirement village legislation has been amended, with further amendments proposed. These legislative changes are not a “magic bullet” but do provide a greater degree of transparency and go some way towards rebalancing rights between residents and village operators.